2021
DOI: 10.1039/d0cy01801e
|View full text |Cite
|
Sign up to set email alerts
|

Mesoporous carbon nitride supported 5,10,15,20-tetrakis(4-methoxyphenyl)-21H,23H-porphine cobalt(ii) as a selective and durable electrocatalyst for the production of hydrogen peroxide via two-electron oxygen reduction

Abstract: Mesoporous carbon nitride (MCN) is synthesized using mesoporous silica material (MCM-41) as a sacrificial template. 5,10,15,20-Tetrakis(4-methoxyphenyl)-21H,23H-porphine cobalt(II) (cobalt tetramethoxyphenylporphyrin, CoTMPP), which consists of methoxy groups as the electron-rich center is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 79 publications
0
19
0
Order By: Relevance
“…Since H 2 O 2 is a reaction intermediate in ORR, it can (under certain conditions) be the final product of a two-electron reduction process [ 5 , 6 , 7 ]. Ideally, the catalysts for ORR should be active for the HPRR.…”
Section: Introductionmentioning
confidence: 99%
“…Since H 2 O 2 is a reaction intermediate in ORR, it can (under certain conditions) be the final product of a two-electron reduction process [ 5 , 6 , 7 ]. Ideally, the catalysts for ORR should be active for the HPRR.…”
Section: Introductionmentioning
confidence: 99%
“…The atomic ratio of each element and the ratio of chemical bonds are shown in Tables S1−S5. For the N 1s spectra (Figure 3d), four peaks at approximately 398.47, 399.16, 400.66, and 401.31 eV correspond to pyridinic N, Cr−N, pyrrolic N, and graphitic N. 22,40 The presence of the Cr−N bond in Cr-ABIm and Cr-ABIm@BP2000 showed that the Cr atom is embedded in the building blocks of the mixture through the stable coordination bond mode. The Cr 2p 1/2 peak is located at about 586.7 eV (Figure 3e).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…The electrochemical active area (ECSA) of the catalyst was derived from the electrochemical double-layer capacitance (C dl ). The capacitance current of the double layer in the non-Faraday interval corresponding to the cyclic voltammetry curve at different sweep speeds (20,40,60,80, and 100 mV s −1 ) was measured. At 0.125 vs RHE, C dl can be obtained from a function of disk current density and scan rates.…”
Section: ■ Experimental Methodsmentioning
confidence: 99%
“…Mesoporous carbon nitride (MCN) has been evaluated as a support for both metal (Mn, Fe, Co, Ni, Cu, and Zn) phthalocyanine and Co porphyrin ORR catalysts by Singh et al , The MCN was synthesized by a hard templating method to improve the surface area and conductivity of the support. The highest E 1/2 (∼0.05 V) is exhibited by CoPc@MCN in these reports, with a limiting current density < 1.5 mA/cm 2 and n ∼ 1.64 in 0.1 M HClO 4 with rotation.…”
Section: Introductionmentioning
confidence: 99%